Impact of Increasing Food Prices on Dietary Diversity and Consumption Patterns among Students of the University of Dhaka, Bangladesh - Shimul Gupta (Journal of Research in Social Science and Humanities, 2025)
Introduction: Rising food prices, exacerbated by the COVID-19 pandemic, the Ukraine war, and climate change, have emerged as a pressing global issue. In Bangladesh, this has led to significant increases in food costs, impacting various groups, including university students.Objective: This study aimed to examine the effects of rising food prices on the dietary diversity and food consumption patterns of students at Dhaka University, with a focus on Kabi Jasim Uddin Hall canteen due to its standardized management system and accessibility.Method: A qualitative research design was employed, incorporating semi-structured interviews, key informant interviews (KII), and focus group discussions (FGD) to explore students lived experiences and coping mechanisms in response to increased food costs.Results: Findings revealed a notable shift in students’ dietary habits due to financial constraints. Many reported reducing food intake and avoiding non-essential food items. Coping strategies included portion control, skipping meals, and focusing on basic, low-cost food options. These outcomes align with similar studies in other South Asian countries, including India and Pakistan.Conclusion: The study highlights the urgent need to address the impact of food inflation on university students. Recommendations include implementing subsidized food programs, offering financial literacy support, promoting on-campus vegetable gardening, initiating food aid for vulnerable students, and collaborating with canteen authorities for price regulation. These measures aim to improve access to a nutritionally diverse diet and support student well-being amid ongoing economic challenges.